“Un-kinged himself” - Thorup, Mikkel (Passage - Tidsskrift for litteratur og kritik, 2010)
Mikkel Thorup: "“Un-kinged himself” - Amerikanernes baglæns march ind i revolutionen" Abstract Mikkel Thorup: “‘Un-kinged himself’”: The American Backward March into Revolution The article explores legitimization strategies in the American Revolution seeking to understand how they bypassed the inherent illegitimacy of any revolution. Dealing with four seminal texts, two from the pre-revolutionary period and two from the early revolutionary years 1775-6, the article seeks to highlight how the revolutionaries legitimised their revolution as a defense of their inherent rights as free-men, that is, how The American revolution and its monumental political transformation was legitimised as a restorative rebellion only seeking to restore what had been lost or violated.